HUBUNGAN POLA KONSUMSI MAKANAN CEPAT SAJI DENGAN STATUS GIZI PADA REMAJA DI SMP N 1 NGAWEN - ANATASYA HERYANI; Feri Catur Yuliani; Rizal Fajri (CV. ALIM'SPUBLISHING, 2024)
Data from RISKESDAS 2018 Indonesian adolescents aged 15-20 years, found that adolescents consume instant noodles or other instant foods with a prevalence of more than 1 time per day 11.2%, more than 1 to 6 times per week 67.6%, and less than 3 times per month 21.2%. This can cause health problems Objective: This study aims to determine the relationship of fast food consumption patterns with nutritional status in adolescents at SMP N 1 Ngawen. Research method: This research is a type of quantitative correlation. With a cross sectional approach. Sampling using simple random sampling obtained 89 respondents. The instrument used ffq questionnaire and tools using scales and microtoice. Data were analysed using spearman rank. Results: Characteristics of respondents in this study the majority of 14 years (36.0%), female gender 44 (49.4%), male 45 (50.6%), the majority of patterns 45 (50.6%) and consumption of the majority of nutritional status 57 (64.0%). Spearman rank results obtained a value of 0.772 (> 0.05). Conclusion: There is no relationship between fast food consumption patterns and nutritional status in adolescents at SMP N 1 Ngawen.